Srovnání úcinnosti ctyr metod pro izolaci aspergilové DNA z periferní krve - Hrncírová, Katerina; Lengerová, Martina; Kocmanová, Iva; Rácil, Zdenek; Volfová, Petra; Lochmanová, Jana; Dvoráková, Dana; Mayer, Jirí (Klinicka mikrobiologie a infekcni lekarstvi, 2008)
AIM OF THE STUDY: The main goal of this study was to find the best method for Aspergillus DNA isolation from peripheral blood samples. The method should be very effective but not expensive or time consuming to be suitable for routine diagnostics use. MATERIAL AND METHODS: We compared four different methods for Aspergillus DNA isolation - one method with enzymatic lysis of the fungal cell wall and three methods that combine chemical and mechanical lysis (using high speed cell disruption with glass beads). Peripheral blood samples were inoculated with defined amount of Aspergillus fumigatus suspension and used for DNA isolation. Isolated DNA was then quantitatively analyzed with in-house real-time PCR method using specific probe. RESULTS: Enzymatic method seems not to be useful in a routine diagnostics mainly because of its low efficiency and too long processing time. Better could be the methods using both chemical and mechanical cell disruption that can isolate fungal DNA with high efficiency in a relatively short time. CONCLUSIONS: The method using ZR Fungal/Bacterial DNA Kit (Zymo Research, USA) was chosen for routine use in our laboratory because it is cheap, fast and very efficient.
Keywords: DNA fungální; Polymerase Chain Reaction; DNA, Fungal; reagenční diagnostické soupravy; Reagent Kits, Diagnostic; Aspergillosis; Aspergillus fumigatus; Humans; lidé; aspergilóza; polymerázová řetězová reakce